2019
DOI: 10.1109/tmi.2019.2901445
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Approach for Classifying Ischemic Stroke Onset Time From Imaging

Abstract: Current clinical practice relies on clinical history to determine the time since stroke onset (TSS). Imaging-based determination of acute stroke onset time could provide critical information to clinicians in deciding stroke treatment options such as thrombolysis. Patients with unknown or unwitnessed TSS are usually excluded from thrombolysis, even if their symptoms began within the therapeutic window. In this work, we demonstrate a machine learning approach for TSS classification using routinely acquired imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 49 publications
(50 reference statements)
0
57
0
1
Order By: Relevance
“…Another study evaluating various traditional ML models in predicting stroke onset time demonstrated that incorporation of DL features to the models improved AUC compared with the ground truth (ie, a DWI-FLAIR mismatch), with the optimal AUC of 0.765 incorporating logistic regression and DL features of MR imaging and MR perfusion (MRP) images. 50 Lee et al 51 used DWI-FLAIR mismatch to predict stroke onset time ,4.5 hours and found that traditional ML models were more sensitive than stroke neurologists (sensitivity ¼ 48.5% for stroke neurologists vs 75.8% for logistic regression; P ¼ .020; 72.7% for SVM, P ¼ .033; 75.8% for RF, P ¼ .013).…”
Section: Additional Factors In Treatment Selectionmentioning
confidence: 99%
“…Another study evaluating various traditional ML models in predicting stroke onset time demonstrated that incorporation of DL features to the models improved AUC compared with the ground truth (ie, a DWI-FLAIR mismatch), with the optimal AUC of 0.765 incorporating logistic regression and DL features of MR imaging and MR perfusion (MRP) images. 50 Lee et al 51 used DWI-FLAIR mismatch to predict stroke onset time ,4.5 hours and found that traditional ML models were more sensitive than stroke neurologists (sensitivity ¼ 48.5% for stroke neurologists vs 75.8% for logistic regression; P ¼ .020; 72.7% for SVM, P ¼ .033; 75.8% for RF, P ¼ .013).…”
Section: Additional Factors In Treatment Selectionmentioning
confidence: 99%
“…Instead of predicting the future, one can also use ML to go back in time and estimate the date at which the disease started. For instance, Ho et al [12] distinguished patients with time-sincestroke lower or higher than 4.5 hours from diffusion, perfusion and FLAIR MRI.…”
Section: Predicting Evolutionmentioning
confidence: 99%
“…Computer-aided diagnosis has moved from the discrimination between a single disease and controls to differential diagnosis [4*-8]. In addition to diagnosis, models for predicting the subsequent evolution of patients have been developed [9][10][11][12][13]. Most of the initial work focused on neuroimaging as the data source, because it is inherently digital and databases are easy to access.…”
Section: Introductionmentioning
confidence: 99%
“…These are mostly based on deep learning yet also include texture analysis using radiomics 50 or fractal analysis. 51 In brief, deep learning has been successfully applied to several fields using convolutional neural networks: scoring knee osteoarthritis on radiographs, 52 improving detection of wrist fractures on radiographs, 53 detecting breast cancer on mammograms, 44 augmenting the ability of radiologists to detect cancer on screening mammograms without increased reading times, 54 classifying breast masses on ultrasound, 55,56 prioritizing the worklist of radiologists for suspected intracranial bleeding on CT, 57 detecting and possibly sub-classifying intracranial bleeding on CT, 58 identifying critical findings on head CT with somewhat limited sensitivity for stroke, 59 predicting ischemic stroke onset time on MR imaging, 60 classifying six common liver tumor entities, 61 triaging chest radiographs for urgent findings, 62 pulmonary nodule detection on chest radiographs, 63 and predicting 2-year survival in patients with non-small cell lung cancer based on standard-of-care CT images of the chest. 64…”
Section: Impact Of the Bionic Radiologistmentioning
confidence: 99%